Astrocaryum ulei (Arecaceae) newly discovered in Peru - Kahn, Francis (2009)
Astrocaryum ulei, previously known from Brazil and Bolivia, is here reported from Madre de Dios in Peru. Based on the new material collected it has been possible to write an amended description of this species, which is presented here.